Protecting Sex: Sexual Disincentives and Sex-Based Discrimination in Nguyen v INS - Weinrib, Laura (Columbia Journal of Gender and Law, 2003)
Catharine MacKinnon’s famous formulation of the social and political struggle between men and women as a manifestation of men’s sexual subordination of women has informed feminist debate for the past two decades. The fundamental project of radical feminism was to demonstrate that sex discrimination and sexual domination are one and the same. Against this backdrop, recent developments in feminist and queer theory have turned the equivalence of sex and sexuality inside out-a dissociation that has played out prominently in the context of legal scholarship, particularly with respect to rape, pornography, and sexual harassment. This effort to rehabilitate “deviant” sexuality entails rescuing the fight against sex discrimination from the vilification of sex. Whatever one’s feelings on the relationship between sex and sex- based discrimination, they are likely to be reserved for academic debate. The successful application of equal protection doctrine to such sex-laden topics as birth status, contraception, and abortion has had the unfortunate side-effect of submerging judicial discussion of sexual subordination and sexual freedoms in favor of less contentious issues of biological equality and difference. The blanket omission of sexuality from sex discrimination decisions-despite the sustained theoretical frenzy surrounding the issue is striking.